Emergency Department Visits in the United States for Pediatric Depression: Estimates of Charges and Hospitalization. (September 2014) - Sun, Diana; Abraham, Ivo; Slack, Marion; Skrepnek, Grant H.; Walthall, Jennifer
Abstract Objectives The objective of this study was to calculate national estimates of depression‐related emergency department (ED) visits and associated health care resource use among children and adolescents 17 years or younger. Another goal was to explore the effects of certain sociodemographic and health care system factors and comorbidities on ED charges and subsequent hospitalization in the United States. Methods The authors analyzed data from the 2006 and 2009 National Emergency Department Sample (NEDS), the largest source of U.S. ED data. ED visits with all listed diagnoses (i.e., principal diagnosis plus secondary conditions) of depression were identified using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes 293.83, 296.2X, 296.3X, 300.4, and 311. Population‐based estimates of ED visits, hospitalization, resource use, comorbidities, and demographics associated with pediatric depression were calculated. Potentially significant covariate associations were also explored using ED charges and hospital admission from the ED. Results The 2006 and 2009 NEDS sample contained 365, 713 ED visits for pediatric depression; the majority were made by adolescents (87.9%). Of these, 27.2% were admitted to the hospital, 69.5% were treated and released, and <0.1% died in ED. The ED charges in 2012 U.S. dollars summed to a hospital bill of $443.8 million, with the ED plus inpatient charges ($1.2 billion) being more than double that amount. The median inpatient length of stay (LOS) was 4.0 days. Suicide and intentional self‐inflicted injury were attempted by 31.4% of the patients. Attention‐deficit, conduct, and disruptive disorders; anxiety disorders; substance use disorders; asthma; and infections were the most common comorbidities. In year 2009, a higher number of diagnoses, older age, being female, key comorbidities, and suicide and intentional self‐inflicted injury were significantly associated with higher ED charges (all p < 0.05). Increased odds of hospital admission from the ED were significantly associated with a higher number of diagnoses, key comorbidities, and suicide and intentional self‐inflicted injury (all p < 0.05). Conclusions Pediatric depression is common in the ED and is associated with significant burden to the health care system. Certain factors such as a higher number of diagnoses, key comorbidities, and suicide and intentional self‐inflicted injury are associated with increased health care costs and resource use. Special attention should be given to these factors, when present.